Analysis of images, social networks and texts : 8th International Conference, AIST 2019, Kazan, Russia, July 17-19, 2019 revised selected papers /: 8th International Conference, AIST 2019, Kazan, Russia, July 17-19, 2019 revised selected papers. (2020) - Unknown
No abstract available